Case report: Bilateral damage to the immature optic radiation and secondary massive loss of retinal ganglion cells causing tunnel vision - Nilsson, Maria; Lennartsson, Finn; Öhnell, Hanna Maria; Gränse, Lotta; Jacobson, Lena (Frontiers in Neuroscience, 2023)
We describe the case of a 30-year-old woman, who needed a formal report on her visual impairment to seek support from society. She was born preterm, and during her neonatal period, she suffered from bilateral intraventricular hemorrhage (IVH) grade 3, a condition that can cause cerebral visual impairment (CVI) due to damage to the retro-geniculate visual pathways. Individuals with such brain damage of this severity are often restricted by cerebral palsy (CP) and intellectual disability, and thus have a limited ability to cooperate in the assessment of visual function. However, our patient was capable of providing reliable test results, and she manifested only a small island of central vision in each eye, with additional reduced visual acuities. She cooperated well in examinations involving MRI of the brain, optical coherence tomography (OCT) of retinal ganglion cells, and multi-focal visual evoked potentials, with each test providing information about potential limitations in the structural prerequisites for visual function. What distinguishes our case is the severity of the damage to the optic radiations and the massive secondary loss of most of her retinal ganglion cells (GCs). However, there is some measurable visual function, which may be due to developmental neuroplasticity during early development, when surviving GCs prioritize the central visual field. Despite her visual difficulties, she is a keen portrait painter. Our patient may be representative of, and a spokesperson for, other individuals with extensive brain damage of the same etiology, who are unable to perform perimetric tests and therefore run the risk of not being recognized as severely visually impaired, and consequently, not being given the best conditions for habilitation. OCT may serve as a helpful diagnostic tool. Aim: This study aims to describe visual behavior and practical applications of visual function in relation to structural prerequisites for visual function.